King Faisal I’s position from Najdi-Hijazi conflict (1921–1925) - Haider, Assist. Lect . Karar (Basra studies journal, 2026)
has This research examines King Faisal I’s attitudes about the Najdi-Hijazi conflict for the period 1921 and 1925, one of the most sensitive periods in the history of the modern Arab East. It seeks to analyze his policy in light of the complexities of a period that combined waning Hashemite ambitions with the rise of Najdi power under the leadership of Abdulaziz Al Saud, within a regional environment subject to British hegemony. The research demonstrates that king Faisal attempted to balance his familial commitment to his father and brother in Al- Hijaz with his political responsibilities as king of an emerging state subject to the constraints of the British Mandate, preferring caution and realism to direct confrontation. It also demonstrates that Faisal’s stance embodied an early awareness of the geopolitical changes that were redrawing the map of the Arabian Peninsula. By tracing his diplomatic stances, his correspondence with British representatives, and his government’s handling of tribal and religious issues, the research reveals that he sought to protect the stability of Iraq without becoming directly involved in the problems and conflicts of the Hijaz. His policies eventually shifted from emotional support for the Hejaz to de facto recognition of the Al Saud authority, which later paved the way for balanced relations between Iraq and Saudi Arabia. The study concludes that King Faisal I’s stance represents a rare experiment in modern Arab history, combining national affiliation with political pragmatism. Faisal lost Hashemite influence in the Hejaz, but he preserved the Iraqi state and laid the foundations for its regional policy, which would endure for decades to come.